2016
DOI: 10.2298/bah1602133k
|View full text |Cite
|
Sign up to set email alerts
|

Composition of raw milk from conventional and organic dairy farming

Abstract: Possible differences between composition of raw milk due to dairy farming system (organic vs conventional) as well as seasonal variations were investigated. The samples were analysed during one year. A total of 6.782 samples of raw milk were collected (4.496 from organic farming). Dairy farms were located in the northern part of Republic of Serbia (Province of Vojvodina). The principle of analysis of raw milk samples was in accordance with the methodology by midinfrared spectrometry and flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Studies comparing the effect of pasture versus TMR feeding systems on the milk fat content have demonstrated that milk produced from TMR systems has a lower or depressed milk fat content [65,66,67,68,69,70]. This observation has been attributed to the high fiber content of a pasture diet in addition to the abundance of materials that induce fat synthesis in the mammary gland, as opposed to TMR diets that differ from fresh pasture systems in their starch content.…”
Section: Impact Of Feeding System On the Lipid Fraction Of Bovine mentioning
confidence: 99%
“…Studies comparing the effect of pasture versus TMR feeding systems on the milk fat content have demonstrated that milk produced from TMR systems has a lower or depressed milk fat content [65,66,67,68,69,70]. This observation has been attributed to the high fiber content of a pasture diet in addition to the abundance of materials that induce fat synthesis in the mammary gland, as opposed to TMR diets that differ from fresh pasture systems in their starch content.…”
Section: Impact Of Feeding System On the Lipid Fraction Of Bovine mentioning
confidence: 99%
“…In this regard, there is a significant difference in the diet of dairy cows in OF vs CF from early spring until early winter. Additionally, milk produced in organic dairy farming has a significantly more concentration of UFA, especially polyunsaturated fatty acid (PUFA) than in conventional farming (KUČEVIĆ & al [3];POPOVIĆ-VRANJEŠ & al [8]). Effects of season, access to fresh grazing, or usage of specific silage types could be used by producers to enhance the content of beneficial FA in milk.…”
Section: Hierarchical Cluster Analysismentioning
confidence: 99%
“…Primarily due to the successful management of dairy cow's feeding in all stages of production. Managing nutrition, as well as a choice of farming system, can contribute to the control of fatty acids content in milk during the year in all seasons (ELLIS & al [5]; KUČEVIĆ & al [3]; POPOVIĆ-VRANJEŠ & al [8]). Useful information about FA content is one of the best approaches to improving a milk quality.…”
Section: Linear Univariate Regression Modelingmentioning
confidence: 99%
See 2 more Smart Citations